(untitled) (Research, Society and Development, 2025)
To evaluate female biomedical students´ body and facial acceptance profile at the Universidade Paranaense Campus Cascavel. After authorization from the Ethics Committee, 129 participants of the biomedicine course were interviewed through an online questionnaire that explored the profile of the body and facial acceptance and possible aesthetic interventions among the students. The results showed that 93.5% of the participants were between 18 and 28 years old; 34.1% of the sample pointed out that it depends on the day to be satisfied with their bodies and faces; 26.4% identified with mannequin four on the Stundark silhouette scale; On the other hand, when asked about body perception through the eyes of another person, 20.9% signaled mannequin two and 20.9% mannequin three; 47.3% of the participants reported that sometimes the evaluation of people close to them can influence self-esteem; 96.1% agreed that after performing aesthetic procedures they can change the way they act and think; 31% of the sample showed interest in performing aesthetic procedures such as plastic surgery; A large part of the sample showed interest in interventions that promise and provide quick results; 55.8% already idealize aesthetic standards displayed by the media and 53.5% seek indication of professionals to perform such procedures. The study concludes that, despite the great interest in aesthetic procedures shown by the students, there are still gaps to be addressed. The commercialization of the perfect appearance is indeed the biggest responsible for body dissatisfaction, but finding the balance between aesthetics and health is vital to achieve body and facial acceptance safely.